Fatal congenital tuberculosis owing to late diagnosis of maternal tuberculosis: case report and review of congenital tuberculosis in China. (2nd July 2020) - Sun, Jing-min; Wang, Chang; Jin, Dan-qun; Deng, Fang
ABSTRACT: Congenital tuberculosis (TB) is rare and the prognosis is poor if not detected early. The diagnosis is often delayed owing to non-specific clinical presentation, misdiagnosis and undiagnosed maternal TB during pregnancy. A 12-day-old girl presented with a 5-day history of fever, cough, poor feeding and respiratory distress. Her mother had a cough and fever at 30 weeks gestation which was managed empirically as community-acquired pneumonia without a TB workup. Immediately postpartum, her mother developed a high fever and shortness of breath and required admission to the intensive care unit. The infant was separated from her mother after delivery. The infant's chest radiograph showed bilateral miliary nodules. Thoracic and abdominal computed tomography (CT) showed multiple enlarged lymph nodes and congenital TB was suspected. Early morning gastric aspirate and sputum (obtained through a suction tube) were positive for acid-fast bacilli on smear microscopy and subsequently Mycobacterium tuberculosis was cultured from both specimens. Lumbar puncture was performed and cerebrospinal fluid (CSF) was compatible with TB meningitis. TB-polymerase chain reaction (TB-PCR) was positive. Her mother was diagnosed with miliary TB on postpartum day 17. Both were given anti-TB chemotherapy. Unfortunately, despite the treatment, the infant died from multiple organ dysfunction syndrome (MODS) caused by congenital TB at the age of 14 days. This case highlights the importance of screening pregnant women for TB in regions where it is highly prevalent. A high index of suspicion of maternal and congenital TB is critical to early diagnosis, especially in such regions.